How Shakespeare’s works have been reinterpreted, adapted and reshaped: a bibliometric review and trend analysis of Shakespeare studies from 2000 to 2023 - Xintong Li; Sihan Li (Humanities & Social Sciences Communications)
Abstract Since transitioning into the post-theory era in 2000, Shakespearean studies have increasingly attracted interdisciplinary attention, engaging fields such as literature, performance studies, digital humanities, and cultural studies. Despite this broad interest, the discipline often lacks a cohesive framework to integrate these perspectives effectively. This study addresses this issue by applying bibliometric methods to data from the Web of Science Core Collection, using tools like VOSViewer and CiteSpace for analysis and visualization. By examining how Shakespeare’s works have been reinterpreted and adapted across diverse cultural and temporal contexts, the research employs the TCCM (Theory, Context, Characteristic, Methodology) framework to analyze thematic developments and interdisciplinary scope in Shakespeare studies from 2000 to 2023. Key findings reveal recurring research themes, including canonical text analysis, gender and performance, cross-cultural dissemination, adaptation, and the growing influence of digital humanities. The study identifies four distinct phases in the evolution of the field: the Initial Phase (2000–2005), focused on textual authenticity and literary value; the Transition Phase (2005–2010), marked by the integration of cultural studies and gender theory; the Mature Phase (2010–2019), exploring societal issues such as ethics and environmental humanities; and the Post-Pandemic Phase (2019–2023), emphasizing globalization and environmental concerns. These phases reflect shifts in academic priorities, methodologies, and interdisciplinary approaches, demonstrating the field’s responsiveness to global and technological developments. This study highlights the importance of deepening interdisciplinary integration and adopting emerging frameworks, such as new materialism, while combining distant and close reading techniques. These approaches offer a nuanced understanding of Shakespeare’s works, showcasing their enduring relevance and cultural transformation in a globalized and rapidly evolving academic landscape.